A tunable massless membrane metamaterial for perfect and low-frequency sound absorption. (17th February 2021) - Xu, Qishan; Qiao, Jing; Sun, Jiayue; Zhang, Guangyu; Li, Longqiu
Abstract: Membrane acoustic metamaterial which is composed of a prestressed membrane and attached mass attracts considerable attention for its low-frequency (<500Hz) sound absorption/isolation. However, its practicality and adjustability are limited by the complicated manufacturing process and the weak robustness and tunability due to the prestressing force of the membrane and attached mass. To overcome this, we propose a sound absorber based on massless membrane-type acoustic metamaterial consisting of a free membrane, supporting grating, and a back cavity. And then, the absorption performance, energy conversion mechanism, and flexible tunability are investigated theoretically and experimentally. It is found that the absorber can achieve nearly perfect sound absorption with a wide bandwidth below 500 Hz. In addition, we can tune acoustic performance through simple and flexible methods. The proposed absorber is expected to be applied in noise control such as noise reduction of mechanical equipment and architectural acoustic.